Cytokine Signature in Schnitzler Syndrome: Proinflammatory Cytokine Production Associated to Th Suppression - Masson Regnault, Marie; Frouin, Eric; Jéru, Isabelle; Delwail, Adriana; Charreau, Sandrine; Barbarot, Sébastien; Néel, Antoine; Masseau, Agathe; Puéchal, Xavier; Kyndt, Xavier; Gayet, Stephane; Lifermann, François; et al. (Frontiers in Immunology, 2020)
Background – Schnitzler syndrome (SchS) is a rare autoinflammatory disease characterized by urticarial exanthema, bone and joint alterations, fever and monoclonal IgM gammopathy. Overactivation of the interleukin(IL)-1 system is reported, even though the exact pathophysiological pathways remain unknown. Objective – To determine ex vivo cytokine profiles of Peripheral Blood Mononuclear Cells (PBMC) from SchS patients prior to treatment and after initiation of anti-IL-1 therapy (anakinra). The sera cytokine profile was studied in parallel. Methods – We collected blood samples from thirty-six untreated or treated SchS. PBMCs were cultured with and without LPS or anti-CD3/CD28. Cytokine levels were evaluated in serum and cell culture supernatants using Luminex technology. Results –Spontaneous TNFα, IL-6, IL-1β, IL-1α and IL-1RA release by PBMCs of SchS patients were higher than in controls. LPS-stimulation further induced the secretion of these cytokines. In contrast, after T-cell stimulation, TNFα, IL-10, IFNγ, IL-17A and IL-4 production decreased in SchS patients compared to healthy controls, but less in treated patients. Whereas IL-1β serum level was not detected in most sera, IL-6, IL-10 and TNFα serum levels were higher in patients with SchS and IFNγ and IL-4 levels were lower. Of note, IL-6 decreased after treatment in SchS (p=0,04). Conclusion – Our data strengthen the hypothesis of myeloid inflammation in SchS, mediated in particular by IL-1β, TNFα and IL-6, associated with overproduction of the inhibitors IL-1RA and IL-10. In contrast, we observed a loss of Th1, Th2 and Th17 cell functionalities that tends to be reversed by anakinra.